1994
DOI: 10.1038/hdy.1994.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest fragmentation on the spatial genetic structure of Acer saccharum Marsh. (sugar maple) populations

Abstract: To examine the effects of forest fragmentation on within-population genetic structure of Acer saccha rum, the spatial distributions of allozyme variation in the first-year seedling cohorts of four forest patch populations (patches) were compared with those of four populations within continuous forest (controls). Forest patch populations exhibited less spatial mixing of genotypes than controls at the smallest scale examined (10-14.1 m), possibly as a result of reduced overlap of seed shadows in patches, which g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 24 publications
3
67
2
5
Order By: Relevance
“…In two French populations only five out of 35 and two out of 20 significant SNDs were found. Similar patterns have been found for the coniferous species Pinus contorta (Epperson & Allard, 1989), Picea mariana (Knowles, 1991), Picea abies (Leonardi et a!., 1996) and for the broadleaved species Acer saccharum (Perry & Knowles, 1991;Young & Merriam, 1994), Quercuspetraea and Q. robur (Bacilieri et al, 1994). In this study most genotypes were apparently randomly located within the population.…”
Section: Discussionsupporting
confidence: 85%
“…In two French populations only five out of 35 and two out of 20 significant SNDs were found. Similar patterns have been found for the coniferous species Pinus contorta (Epperson & Allard, 1989), Picea mariana (Knowles, 1991), Picea abies (Leonardi et a!., 1996) and for the broadleaved species Acer saccharum (Perry & Knowles, 1991;Young & Merriam, 1994), Quercuspetraea and Q. robur (Bacilieri et al, 1994). In this study most genotypes were apparently randomly located within the population.…”
Section: Discussionsupporting
confidence: 85%
“…Forest management practices have also been shown to increase genetic structure compared with natural forests, especially if the breeding practices imply drastic reduction of the effective population size (Young and Merriam, 1994;Finkeldey and Ziehe, 2004). Population size reduction could potentially increase the rate of selffertilization because of the reduction in number of local compatible mates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, human activities may also have an impact on the genetic structure of various species [65][66][67]. However, the results of the present study showed that among the 19 Q. variabilis populations, the population in the center of the distribution did not experience a bottleneck effect, whereas three populations at the periphery (FJ, PS, CZ) did, and three genetic lineages (cluster I,II and III) obtained from STRUCTURE showed distributions in every population (Figures 4 and 5).…”
Section: Genetic Differentiationmentioning
confidence: 99%